Analítica dos dispositivos de poder presentes nas práticas de gestão em recursos humanos - Toscano, Mateus Miguel Salvador (2006)
Changes of the practical ones in the daily one of the companies affect the life, not only of its employees, but of the social body. This form, to affect the people and being affected for them, used in the organizations, for times passes unobserved, as muc